Human Capital Challenges in Sustainability Start-ups- Attracting, Retaining, and Developing Talented Individuals (Global Journal of Management and Business Research, 2024)
Abstract not found
Keywords: sustainability start-ups; human capital challenges; attracting talent; retaining talent; developing talent; performance